Diversity and Ressentiment in Educating for LGBTQ-friendly Changes in a University - Rod P. Githens (Adult Education Research Conference, 2009)
Within universities, lesbian, gay, bisexual, transgender, and queer (LGBTQ) individuals have used education to seek equitable policies and improve campus climates. In this project, I examine the approaches to diversity education by LGBTQ activists seeking domestic partner benefits within a major state university system.